Effects of Cadmium Sulfate on the Brown Garden Snail Cornu aspersum: Implications for DNA Methylation - Marius Georgescu; George Andrei Drăghici; Eliza-Florentina Oancea; Cristina Adriana Dehelean; Codruţa Şoica; Nicolae-Valentin Vlăduţ; Dragoș Vasile Nica (Toxics, 2021)
An extensive literature exists regarding the cellular, physiological, and genetic effects of cadmium (Cd)—A highly toxic, but commonly used trace metal in modern industry. However, limited data are available on its epigenetic effects, especially for terrestrial sentinel invertebrates. We determined Cd retention, total DNA methylation, and the methylation status of 5′ end of the Cd-MT gene in the hepatopancreas of the brown garden snail, Cornu aspersum, fed Cd sulfate for four weeks. Bodyweight changes and survival were also measured. Hepatopancreas cadmium increased in a dose-dependent manner from the third-lowest dose onward, with very large amounts being found for the highest treatment group. However, no mortalities occurred, irrespective of dietary Cd dose. We identified significant genome-wide hypermethylation in specimens given the highest dose, which overlapped with a significant bodyweight decrease. The Cd-MT gene showed an unmethylated 5′ end of the Cd-MT gene and this status was not affected by cadmium exposure. Hepatopancreas DNA methylation is as sensitive as bodyweight to non-lethal concentrations of dietary Cd given as cadmium sulfate but less responsive than tissue accumulation. Such an exposure event, by contrast, does not affect the methylation status of the Cd-MT gene 5′ end.